Analysis of Dental Collagen Cross-Linking and Carbonate Mineral Integration from Roman/Byzantine Sites in Jordan Using ATR-FTIR Spectroscopy: ATR-FTIR analysis of human dentine (Bulletin of the International Association for Paleodontology, 2024)
Existing bioarchaeological studies have not deeply explored the analytical characterization of the chemical structure of dentine. Accordingly, this study used ATR-FTIR to analyze the dentine of 30 human teeth from six archaeological sites in Jordan dated from the Early Roman to the Early Byzantine periods. Besides collagen cross-linking, the factors (ratios) that may influence the strength of dentine were also analyzed and include the ratios of phsphate/amide I, crbonate/phosphate, and A-type cabonate/B-type carbonate. The results of the study point to statistically insignificant diffrences in the factors affectng tensile strength of dentine and thus teeth loading on the site level, while a statistically significan one is found among sites. The differences in these ratios is found to be attributed tooth loading and age at death.